2002
DOI: 10.1037/0735-7036.116.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Multiple environmental contexts and communication in pygmy marmosets (Cebuella pygmaea).

Abstract: There are multiple components to the concept of Umwelt experienced by an organism that may constrain the type and structure of communication signals as well as the usefulness of these signals. To illustrate the impact of these multiple environmental components, the authors used signals of the pygmy marmoset (Cebuella pygmaea), a small primate from the western Amazon. The authors summarize studies to show how the physical effects of the habitat; effects of other species, both predators and nonpredators; anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 40 publications
(65 reference statements)
0
26
0
1
Order By: Relevance
“…Data for human juveniles and young adults were unavailable for comparison, but studies of human language acquisition have shown that developing humans go through stages of echolalia (continuous repetition) at both the phonemic and the word levels that correspond to the redundancy observed at analogous stages in dolphin and squirrel monkey vocal development (for review, see Locke, 1993). This pattern was predicted in McCowan et al (1999) for these and other species in which learning plays an important role in vocal development (for review, see King et al, 2002;Locke, 1993;McCowan & Newman, 2000;McCowan & Reiss, 1995b;Reiss & McCowan, 1993;Snowdon & de la Torre, 2002;Snowdon & Hausberger, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for human juveniles and young adults were unavailable for comparison, but studies of human language acquisition have shown that developing humans go through stages of echolalia (continuous repetition) at both the phonemic and the word levels that correspond to the redundancy observed at analogous stages in dolphin and squirrel monkey vocal development (for review, see Locke, 1993). This pattern was predicted in McCowan et al (1999) for these and other species in which learning plays an important role in vocal development (for review, see King et al, 2002;Locke, 1993;McCowan & Newman, 2000;McCowan & Reiss, 1995b;Reiss & McCowan, 1993;Snowdon & de la Torre, 2002;Snowdon & Hausberger, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…This pattern may also have a more functional basis that requires developmentally adaptive strategies for different age groups (Hersek & Owings, 1994;Owings & Loughry, 1985). Further research is needed to determine whether young infant dolphins or squirrel monkeys obtain specific benefits from perceivers by producing more diversely structured repertoires than older infants and adults (see Locke, 1993, for evidence in the babbling of humans; see Snowdon & de la Torre, 2002, for evidence in the babbling of marmosets).…”
Section: Resultsmentioning
confidence: 99%
“…Upon seeing a silhouette of a predator, male chickens (Gallus gallus) are more likely to emit context-specific alarm calls if there is a potential mate present rather than another male chicken or a female of another species (Karakashain, Gyger, & Marler, 1988). Pygmy marmosets (Cebuella pygmaea) alter the acoustic structure of their contact calls based on the distance of their audience (Snowdon & de la Torre, 2002). Similarly, vervet mothers are more likely to produce alarm calls when with their own offspring than with unrelated juveniles (Cheney & Seyfarth, 1985).…”
Section: Caller Goalmentioning
confidence: 99%
“…The perceptual abilities of predators can influence signal design on both the evolutionary and proximate time scales (Owings et al 2002; Snowdon & de la Torre 2002). It is unlikely, however, that rodent ultrasonic communication evolved because of its inaudibility to rodents’ wide array of potential predators.…”
Section: Predator Avoidancementioning
confidence: 99%